2015
DOI: 10.1016/j.cattod.2014.03.077
|View full text |Cite
|
Sign up to set email alerts
|

From the powder to the honeycomb. A comparative study of the NSR efficiency and selectivity over Pt–CeZr based active phase

Abstract: The efficiency and the selectivity of a model platinum based catalyst supported on a modified ceria-zirconia oxide was evaluated in the NOx storage-reduction (NSR) process at four catalytic scales: powder, (0.5"x1.5") flow-through monolith (FTM) system, small size (1"x2") and full size (5.66"x10") catalysed Diesel Particulate Filter (DPF). The washcoating of the active phase over FTM affects both the NOx storage properties and the NOx reduction step. The reduction step efficiency is especially decreased at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In some cases, differences in the catalytic behavior when going from the powder to the monolith have been interpreted in terms of physicochemical features related with the upscaling, e.g. : diffusion limits [5]. However, recent studies have evidenced that the spatial distribution of the different constituents of multicomponent catalysts based on ceria and the compositional features of the surface layer of the corresponding monoliths were significantly influenced by the washcoating process [6].…”
Section: Introductionmentioning
confidence: 98%
“…In some cases, differences in the catalytic behavior when going from the powder to the monolith have been interpreted in terms of physicochemical features related with the upscaling, e.g. : diffusion limits [5]. However, recent studies have evidenced that the spatial distribution of the different constituents of multicomponent catalysts based on ceria and the compositional features of the surface layer of the corresponding monoliths were significantly influenced by the washcoating process [6].…”
Section: Introductionmentioning
confidence: 98%
“…Cerium oxides have been also studied for NOx removal in Diesel exhausts using the NSR technology [9][10][11], where NOx is stored on the catalyst and a reductant is fed periodically into the exhaust gas stream to reduce the stored NOx species. It has been reported that the NSR performance of Pt/Ceria is improved upon doping ceria with Pr, because Pr accelerates the oxidation of adsorbed NOx species and destabilizes these species when the reductant is fed [12].…”
Section: -Introductionmentioning
confidence: 99%